2014
DOI: 10.1259/dmfr.20140090
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of the bifid mandibular canals and retromolar foramina: cone beam CTvspanoramic radiography

Abstract: Objectives: To examine the presence and morphologic characteristics of bifid mandibular canals (BMCs) and retromolar foramens (RFs) using cone beam CT (CBCT) and to determine their visualization on panoramic radiographs (PANs). Methods: A sample of 225 CBCT examinations was analysed for the presence of BMCs, as well as length, height, diameter and angle. The diameter of the RF was also determined. Subsequently, corresponding PANs were analysed to determine whether the BMCs and RFs were visible or not. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 37 publications
8
64
3
3
Order By: Relevance
“…is finding has been commonly reported in previous studies as well [12,13,33,37,40,41]. In this study, bilateral retromolar canals were found in 5.5% of the cases, which have also been commonly reported by some previous studies [12,15,16,25,36,41].…”
Section: Discussionsupporting
confidence: 88%
“…is finding has been commonly reported in previous studies as well [12,13,33,37,40,41]. In this study, bilateral retromolar canals were found in 5.5% of the cases, which have also been commonly reported by some previous studies [12,15,16,25,36,41].…”
Section: Discussionsupporting
confidence: 88%
“…The presence of RMC has been reported by some authors in different populations, showing its increasing incidence [2][3][4][5] . There have only been a few published studies on this subject and there is no current systematic review on the prevalence of RMC and its clinical implications, namely risk of inferior alveolar nerve block failures, accidents and surgical complications such as paresthesia and hemorrhage 9,10 .…”
Section: Introductionmentioning
confidence: 77%
“…There may be several extraosseous branches of the inferior dental nerve prior to penetration through the mandibular canal, and such variations may be associated with the presence of accessory foramens and multiple canals 2,3 . A significant correlation has been observed between RMC and the accessory mandibular foramen 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, cadaveric studies have reported a prevalence ranging from 8.3% to 52.0% using CBCT images, and 8.0% to 40.4% with microscopy (Kikuta et al ). The RMC's average diameter was 1.58 mm (range, 1.13–2.24 mm) (Kuribayashi et al ; Senthil Kumar and Kesavi ; Han and Hwang ; Muinelo‐Lorenzo et al ; Capote et al ; Sisman et al ; Motamedi et al ).…”
Section: Literature Review and Suggestions For Risk Assessment Of Injurymentioning
confidence: 99%